KEPEMIMPINAN KEPALA DESA DALAM PENGELOLAAN PROGRAM 2019 UNTUK PELAYANAN PUBLIK DI DESA TARO (KAJIAN KOMUNIKASI POLITIK) - I Wayan Sedia; I Nyoman Yoga Segara; I Wayan Wastawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
In the midst of budget constraints, the village head of Taro in 2019 has achieved a lot of success in his services to the community in the village of Taro. Such as, through the road infrastructure program can reduce unemployment and poverty, online population administration programs, rural tourism development programs that obtain champions of national hope, awards Kalpataru and the Women's Farmers Group Program (KWT) won first place in the province. The method used in data collection is observation or observation by researchers, researcher interviews with respondents, documentation that is by collecting writings, photos of research sites and literature, especially those in the literature of the Hindu Dharma Negeri Denpasar State Institute. Data analysis techniques in this study used descriptive qualitative which emphasizes the meaning of the phenomena that arise with content analysis. This analysis emphasizes the importance of messages in verbal and nonverbal communication. A qualitative descriptive method with a content analysis approach, to understand political communication carried out by the village head of Taro. Â Based on the results of research conducted, the Taro village head in his leadership used a political communication strategy through the implementation of the vision and mission of the Taro village government with a work program. Collaboration that has been carried out with government agencies, customs, community groups, and mass media and the use of symbols. The function of political communication is carried out by providing information forming networks and providing solutions. The implications of the political communication of the village head can improve the welfare of the community and the progress of the Taro village.